Enantioselective synthesis of functionalized pyrazoles by NHC-catalyzed reaction of pyrazolones with alpha,beta-unsaturated aldehydes - Yetra, Santhivardhana Reddy; Mondal, Santigopal; Suresh, Eringathodi; Biju, Akkattu T. (Organic Letters, 2015)
The N-heterocyclic carbene (NHC)-organocatalyzed enantioselective annulation reaction of pyrazolones with alpha,beta-unsaturated aldehydes proceeding via the chiral alpha,beta-unsaturated acyl azolium intermediates under oxidative conditions is presented. The reaction afforded dihydropyranone-fused pyrazoles in moderate to good yields and good er values under operationally simple and base-free conditions.